A Complete Response Case in a Patient with Multiple Lung Metastases of Rectal Cancer Treated with Bevacizumab plus XELIRI Therapy - Hashida, Hiroki (Case Rep Oncol, 2017)
It has been reported that many patients with lung metastasis of colorectal cancer (CRC) underwent chemotherapy with fluorouracil, folinic acid, oxaliplatin, irinotecan, or capecitabine. There is a small number of reports about the capecitabine and irinotecan (XELIRI) plus bevacizumab (BV) therapy for patients with metastatic CRC in Japan. We report a case of successful BV+XELIRI therapy for rectal cancer with multiple lung metastases as first-line chemotherapy. A 53-year-old female presented with advanced rectal cancer and metastatic lung tumors. Following surgery, the patient was treated with XELIRI+BV. After 6 courses, a computed tomography scan showed complete response of the lung metastases. No recurrence has occurred for 3 years after chemotherapy was stopped.